Empirical Study on the Optimization Strategy of Subject Metro Design Based on Virtual Reality - Wu, Zhendong (Informatica (Ljubljana), 2018)
A three-dimensional simulation interactive virtual scene was established taking the theme subway in Chengdu and Guangzhou as the typical case, and the standard metro in Xiamen as the reference. An experiment was designed using virtual reality built-in eye movement equipment and following the principle of visual attentiveness. The conscious and unconscious visual behaviors of users were analyzed and the impacts of different design methods on user experience and behaviors were analyzed. This study extracted the key elements of the theme subway design and recombine them to compared the design of facilities at the same position but in different themes and the design of space interface at different positions but in the same theme. Moreover, optimization strategies were put forward for the design of theme subway space to enhance the availability of the design.